1997
DOI: 10.1073/pnas.94.23.12343
|View full text |Cite
|
Sign up to set email alerts
|

Control of alternative pre-mRNA splicing by distributed pentameric repeats

Abstract: Multiple copies of the hexamer TGCATG have been shown to regulate fibronectin pre-mRNA alternative splicing. GCATG repeats also are clustered near the regulated calcitonin-specific 3 splice site in the rat calcitonin͞CGRP gene. Specific mutagenesis of these repeats in calcitonin͞CGRP pre-mRNA resulted in the loss of calcitoninspecific splicing, suggesting that the native repeats act to enhance alternative exon inclusion. Mutation of subsets of these elements implies that alternative splicing requires a minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 15 publications
2
58
1
Order By: Relevance
“…Not all (U)GCAUG elements within a particular transcript have a demonstrable effect on splicing, and it is not immediately obvious what determines the difference. In the case of calcitonin/CGRP, it was shown that only two of the five (U) GCAUG elements, one intronic and one exonic, are needed for proper regulation (17). This mirrors the situation with FGFR2 splicing regulation where deletion of two (U)GCAUG elements within the loop region between IAS2 and ISAR core in FGFR2 transcripts has no effect on cell-type-specific exon inclusion (1,32).…”
Section: Overexpression Of Mfox-2 Coordinately Activates Exon Iiib Inmentioning
confidence: 78%
See 3 more Smart Citations
“…Not all (U)GCAUG elements within a particular transcript have a demonstrable effect on splicing, and it is not immediately obvious what determines the difference. In the case of calcitonin/CGRP, it was shown that only two of the five (U) GCAUG elements, one intronic and one exonic, are needed for proper regulation (17). This mirrors the situation with FGFR2 splicing regulation where deletion of two (U)GCAUG elements within the loop region between IAS2 and ISAR core in FGFR2 transcripts has no effect on cell-type-specific exon inclusion (1,32).…”
Section: Overexpression Of Mfox-2 Coordinately Activates Exon Iiib Inmentioning
confidence: 78%
“…Previously we had identified two overlapping (U)GCAUG elements downstream of ISAR core that were important for both exon IIIb activation and exon IIIc repression (1). Understanding that (U)GCAUG elements generally are present in multiple copies in the same pre-mRNA (8,17,19,20,23,26), we scanned the FGFR2 sequence for other (U)GCAUG elements and found a (U)GCAUG element present in exon IIIc. To determine if this sequence played a role in activating exon IIIb and repressing exon IIIc, we created minigenes where we mutated the overlapping GCAUG elements downstream of ISAR core (C10-18), the (U)GCAUG in exon IIIc (IIIc Mut), or both (C10-18 IIIc Mut) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These proteins each contain a single highly conserved RNA recognition motif (RRM) that binds the sequence (U)GCAUG (Jin et al 2003;Auweter et al 2006;Ponthier et al 2006;Yeo et al 2009). This element serves an important role in controlling the splicing of many alternative exons (Black 1992;Huh and Hynes 1994;Kawamoto 1996;Del Gatto et al 1997;Hedjran et al 1997;Modafferi and Black 1997;Lim and Sharp 1998;Deguillien et al 2001;Baraniak et al 2006). The Fox proteins typically act as splicing activators when bound downstream of an alternative exon, or as silencers when bound upstream (Underwood et al 2005;Zhang et al 2008;Yeo et al 2009).…”
Section: Introductionmentioning
confidence: 99%